(untitled) (CAHIERS MAGELLANES-NS, 2024)
Given the enormous impact that the software industry has on so many facets of our lives today, software projects are extremely important. Digital transformation is driven across industries by software developments. They facilitate the utilisation of technology by organisations to optimise operations, augment productivity, and provide inventive products and services. To be competitive and adjust to the quickly changing market dynamics of today's world, companies must undergo digital transformation by making full use of software projects. Objectives: The main aim of the current study is to determine the main causes of project delay and cost overrun in software projects, identify the effects of project delay and cost overrun on software projects, and define the role of cost estimation models in overcoming project delays and cost overruns in these projects. Results and conclusions:The researcher reviews the literature on causes behind delay and cost overrun and describes the role that can be played by cost estimation models in that process. In light of the reviewed literature, the researcher reaches certain recommendations for the software industry.